Black Chokeberry (Aronia melanocarpa) Juice Supplementation Affects Age-Related Myocardial Remodeling in Rats - Elena Daskalova; Mina Pencheva; Slavi Delchev; Lyudmila Vladimirova-Kitova; Spas Kitov; Stoyan Markov; David Baruh; Petko Denev (Life)
Background: Cardiac aging is associated with myocardial remodeling and reduced angiogenesis. Counteracting these changes with natural products is a preventive strategy with great potential. The aim of this study was to evaluate the effect of Aronia melanocarpa fruit juice (AMJ) supplementation on age-related myocardial remodeling in aged rat hearts. Methods: Healthy male Wistar rats (n = 24) were divided into three groups: (1) young controls (CY)—age 2 months; (2) old controls (CO)—age 27 months; (3) AMJ group—27-month-old animals, supplemented with Aronia melanocarpa juice (AMJ) at a dose of 10 mL∙kg−1 for 105 days. After this period, the hearts of the animals were fixed, embedded in paraffin, and immunohistochemical and morphometric analyses were performed. Results: A higher vascular and capillary density was found in the hearts of the AMJ group, as compared to CO. The mean number of CD34+ cells in the myocardium increased by 18.6% in the AMJ group, as compared to CO (p < 0.05). Furthermore, the angiotensin converting enzyme 2 (ACE2) immunoexpression in the myocardium increased by 37% (p < 0.05) and the Proto-oncogene Mas receptor (MAS1) immunoexpression increased by 6% (p < 0.05) in the AMJ group, as compared to CO. Conclusions: As a result of the application of AMJ, noticeable neovascularization was found, which indicates improved myocardial nourishment. The present study demonstrates for the first time that polyphenol-rich AMJ can positively influence age-related microvascular myocardial remodeling in rats, thus outlining its potential as a preventive agent for healthy cardiac aging.